An evaluated list of Cenozic-Recent radiolarian species names (Polycystinea), based on those used in the DSDP, ODP and IODP deep-sea drilling programs - Lazarus, David; Suzuki, Noritoshi; Caulet, Jean-Pierre; Nigrini, Catherine; Goll, Irina; Goll, Robert; Dolven, Jane K.; Diver, Patrick; Sanfilippo, Annika (Zootaxa, 2015)
A first reasonably comprehensive evaluated list of radiolarian names in current use is presented, covering Cenozoic fossil to Recent species of the primary fossilising subgroup Polycystinea. It is based on those species names that have appeared in the literature of the Deep Sea Drilling Project and its successor programs, the Ocean Drilling Program and Integrated Ocean Drilling Program, plus additional information from the published literature, and several unpublished taxonomic database projects. 1192 names are recognised as valid, and several hundred additional names including synonyms and mispellings are given as well. A brief list of valid names is provided in the main paper, while the full list, with synonyms, author, year of publication, family assignment, geologic age interval and notes is provided as a SOM spreadsheet table.